Learning in action sports: A scoping review. (February 2020) - Ellmer, Eva; Rynne, Steven; Enright, Eimear
Action sports have increased in popularity, particularly over the past two decades. Research in the area has also proliferated, as multiple disciplinary perspectives and theoretical and conceptual frames have been applied to understanding and exploring a host of research questions concerning action sports culture, contexts and participants. However, despite this flurry of research activity, not much is known empirically about the learning of action sport participants, and few studies have focused specifically on learning in action sports. A scoping review was, therefore, conducted with the aim of synthesising the work that has been undertaken, and mapping future research agendas. Informed by Arksey and O'Malley's six-stage framework, leading sports and education databases and Google Scholar were searched for empirical literature on learning in action sports published before July 2018. After the results were screened and relevant studies identified, data were extracted and analysed using a frequency and thematic analysis to form both a descriptive and thematic summary. A total of 78 empirical studies both from the peer-reviewed and grey literature were included in the scoping review. The frequency analysis concerned information on publication year, academic field, study design, study tools, sport and population. The thematic analysis led to the development of five main themes, addressing learning in social, physical, cultural, and cognitive/psychological contexts and via various forms of feedback. The majority of articles on learning in action sports were published from 2010 onward, suggesting a growing interest in the area. More theses/dissertations resulted in peer-reviewed publications; however, less than half of all reviewed journal articles were published in education/pedagogy journals. Theoretical and conceptual frameworks were rarely explicitly referenced and/or lacked clarity. There was consensus that learning in action sports is largely informal and self-regulated. With the increasing professionalisation of many action sports and their inclusion in international competition events and also in national curricula, an increase in more formalised learning is predicted. Finally, learning in action sports can be highly individualistic but only a few studies acknowledged this. A greater variety of research questions and methodologies, and more work across disciplinary boundaries will assist in the generation of new knowledge.